2022
DOI: 10.5713/ab.21.0150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcriptome between high- and low-marbling fineness in longissimus thoracis muscle of Korean cattle

Abstract: Objective: This study compared differentially expressed genes (DEGs) between groups with high and low numbers of fine marbling particles (NFMP) in the longissimus thoracis muscle (LT) of Korean cattle to understand the molecular events associated with fine marbling particle formation. Methods:The size and distribution of marbling particles in the LT were assessed with a computer image analysis method. Based on the NFMP, 10 LT samples were selected and assigned to either high-(n = 5) or low-(n = 5) NFMP groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For longer transcripts with many isoforms or non-poly(A) transcripts, traditional RNA-Seq may be more appropriate. To date, QuantSeq has been deployed in transcriptomic studies of multiple livestock species, including cattle ( Pascottini et al, 2021 ; Beak and Baik, 2022 ; Busato et al, 2022 ; Pedroza et al, 2022 ), sheep ( Kubik et al, 2018 ), chicken ( Ibrahim et al, 2021 ) and pigs ( Dong et al, 2018 ; Kroeske et al, 2021 ; Schroyen et al, 2021 ; Kramer et al, 2022 ).…”
Section: Additional Discussion Pointsmentioning
confidence: 99%
“…For longer transcripts with many isoforms or non-poly(A) transcripts, traditional RNA-Seq may be more appropriate. To date, QuantSeq has been deployed in transcriptomic studies of multiple livestock species, including cattle ( Pascottini et al, 2021 ; Beak and Baik, 2022 ; Busato et al, 2022 ; Pedroza et al, 2022 ), sheep ( Kubik et al, 2018 ), chicken ( Ibrahim et al, 2021 ) and pigs ( Dong et al, 2018 ; Kroeske et al, 2021 ; Schroyen et al, 2021 ; Kramer et al, 2022 ).…”
Section: Additional Discussion Pointsmentioning
confidence: 99%
“…We compared the transcriptomes of high-and low-marbling-fineness groups of longissimus thoracis (LT) muscle from Korean cattle. We identified 328 differentially expressed genes (DEGs), analysis of which revealed that pathways regulating adipocyte hyperplasia and hypertrophy are involved in the marbling fineness of the LT [19].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…At present, studies have screened out differential lncRNAs related to intramuscular fat deposition in muscle samples of beef cattle and other livestock via transcriptome sequencing, and combined this with functional enrichment pathway analysis to regulate the biological processes of intramuscular fat deposition associated with marbling formation. Research has discovered that pathways related to fat proliferation, fat droplet hypertrophy, and adipocyte differentiation are implicated in the formation of marbling patterns in beef cattle muscle tissue [ 15 ]. In Hanwoo beef cattle, three types of samples, namely muscle, intramuscular adipose, and subcutaneous adipose, were taken for RNA sequencing, with the aim of identifying the lncRNAs associated with shear force, body weight, and muscle function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%